Indicadores básicos de salud en el programa NutrIMSS: estudio retrospectivo. - Acosta-Gutiérrez, María Nayeli; Hernández-Torres, Alma Patricia; Escamilla-Nuñez, María Consuelo; Blanco-Muñoz, Julia; Camarillo-Nava, Víctor Manuel; Atrisco-Olivos, Rosaura; Rodriguez-Garcia, Julia del Carmen (Revista Medica del IMSS)
Background: The NutrIMSS program is granted to populations with chronic conditions to improve basic health indicators and its effectiveness in this population is unknown. Objective: To analyze the change in the basic health indicators of patients who attended the NutrIMSS Program, at the UMF No. 2 of the IMSS in Mexico City, during the period 2018 to 2019. Material and methods: From 105 files of IMSS beneficiaries, a retrospective cohort study was carried out considering two measurements, before and after the NutrIMSS program. To evaluate the average change over time of health indicators, GEE models (Generalized Estimation Equations) and multiple linear regression models were used. Statistical analysis was used using the statistical program StataCorp 2015. Results: Patients who attended the Program showed changes between the beginning and end of the period with an average of three months of follow-up. They presented a decrease in the following health indicators: body weight of 1 kg, body mass index: 0.8 kg/m2, glucose of 13 mg/dL, triglycerides of 57 mg/dL and cholesterol of 17 mg/dL (p < 0.005 in all cases). There was no difference in the level of blood pressure. Conclusions: The NutrIMSS program influenced the improvement of the health indicators of the population of the program and is an ally to improve the health of the IMSS beneficiary population.